METHYLENE BLUE AS ANTIDOTE FOR ISCHEMIC PRIAPISM STATUS BY CUMULATIVE ORAL DOSES OF TURKISH VIAGRA PASTE, ADULTERATED WITH SILDENAFIL PASTE, A CASE REPORT (World Bulletin of Public Health, 2024)
Priapism is prolonged and persistent erection of the penis without sexual stimulation. It is an uncommon urological a time –sensitive emergency. Drugs- self-medication of over-the-counter are known causes of priapism. Ayurveda Turkish Viagra paste is illegally imported, commonly over the counter herb used as aphrodisiac. Treatment of priapism varies from a conservative medical to a drastic surgical approach. Treatment; Methylene blue (MB), a guanylate cyclase inhibitor, is a potential inhibitor of endothelialmediated cavernous relaxation. Result; Serial of ayurveda Turkish Viagra paste ‘s samples were emphasized the adulteration them with considerable quantities of Sildenafil by chromatographic analysis charts. Conclusion; Serial therapeutic aspiration of blood from erect penis, followed by intercavernosal injection of Methylene Blue, prompted us to assess the feasibility, use and effectiveness of MB in the treatment of priapism.